Effect of filler loading and chemical modification on properties of low density polyethylene/corn stalk biocomposites - Azimah Ismail (School of Materials Engineering, Universiti Malaysia Perlis, 2014)
In this study, the utilization of corn stalk (CS) as a filler in low density polyethylene (LDPE) was investigated. The effect of CS loading and chemical modification on tensile properties, morphology, water absorption and thermal properties of LDPE/CS biocomposites were studied.